Peran Kepala Sekolah dalam Peningkatan Kompetensi Profesional Guru Tafsir Amaly di SMA Primaganda Bulurejo Diwek Jombang - Asih Wilujeng; Asriana Kibtiyah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2022)
The main role of the principal as an educational leader is to create a teaching and learning situation so that teachers can teach, and students can learn well. In carrying out the role of the principal, the headmaster has a dual responsibility, namely carrying out school administration to create a good teaching and learning situation and carrying out supervision so that teachers increase in carrying out teaching tasks and in guiding the growth of students. Principals who can carry out their functions as educators, managers, administrators, supervisors, leaders, innovators, and motivators can be said to have good leadership abilities. Teachers are one of the factors that affect the quality of education. To improve teacher competence, it is necessary to conduct a testing system for teacher competence. In line with the regional autonomy policy, several regions have conducted teacher competency tests, they do so mainly to determine the ability of teachers in their area, to increase their ranks and positions, as well as to appoint school principals and deputy principals.